Numerical simulations of cancer treatment prediction: modeling the influence of immunity. Issue 1 (May 2021) - Ezaki, Yuka; Nagayama, Katsuya; Miura, Ichiro
Abstract: Malignant tumors, also called cancer or malignant neoplasms, are life-threatening tumors that invade the borders of other tissues or spread to other parts of the body and grow in various locations [1]. Recent evidence suggests that cancer cells generated by genetic mutations are eliminated by immune cells. Immune cells are immune cells that recognize and attack foreign substances, pathogens, and cancers in the body. A decline in immunity due to ageing or nutritional deficiencies, or due to immunosuppression is associated with increased risk of cancer cells [2]. Immunotherapy is a treatment method that activates the body's innate immune function to eliminate cancer cells. This study, therefore, set out to assess the effect of immunotherapy using numerical simulations. Parameters, such as the conditions of cancer cell death with immune cells, cell division, and angiogenesis, were theoretically set and introduced into the model.